Mažosios Lietuvos tautinio sąjūdžio protestantiškojo sparno periodinis leidinys , Pagalba" valdant kaizerinei Vokietijai (iki 1919 m.) - Kaunas, Domas (Knygotyra, 2002)
The Lithuanian national movement in Lithuania Minor was developing in the conditions of intensive activity of German political organisations, cultural integration of both parts of Lithuania (Minor and the Great one), and the strengthening of Lithuanian national autonomy. The National movement of Lithuanian Minor was transforming into a differentiated political movement and independent organisations since the 19" century. A part of them stayed under the influence of German political parties, another part sought the political autonomy. Each of these organisations relied and flocked around ideologically related newspapers: "Lietuviška ceitunga" in Klaipėda, "Konzervatyvus draugystės laiškas" in Priekulė, "Nauja lietuviška ceitunga" in Tilžė and others. The latest to emerge was the Protestant wing of Lithuanian national movement with a periodical "Pagalba" (1904–1939). Vilius Gaigalaitis (1870-1945)- a well-known Lithuanian activists a deputy of Prussian Parliament (landtag), an Evangelical-Lutheran priesi - edited it. This joumal and its editor’s supporters declared tolai loyalty to Kaiser Germany, however, they sought to preserve the identity of Lithuanians in Lithuania Minor through political and cultural activity, cultural cooperation with Great Lithuania, and creation and promotion of a significant image of Lithuanian nation in the world. This led to confrontation with political power in Germany. The cultural, national, and political development of "Pagalba" and its supporters was stopped by the war. The situation, factors of influence and the goals of activity later changed significantly.